Plaintext Related Image Encryption Scheme Using Chaotic Map - Yong Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A plaintext related image blocking encryption algorithm is proposed in this paper, which includes two kinds of operations on inner-block confusion and inter-block diffusion. Firstly, a float-point lookup table need to be generated by iterating chaotic system; Secondly, choose one of the entries in the look-up table as initial value of chaotic system, and iterate it to produce one secret code sequence for inner-block confusion; Thirdly, by using one pixel value of the former block to locate another entry in the look-up table, iterate it to yield another secret code sequence for inter-block diffusion; Finally, through two rounds of the block-by-block processes, the plain-image will be transformed into the cipher-image. The simulation results show that the proposed method has many good characters.DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3482